Genre Criticism as a Plausible Explanation for the Prevalence of Narrativity - Tasevska Hadji Boshkova, Iskra (Ss Cyril and Methodius University in Skopje, Blaze Koneski Faculty of Philology, 2017)
This paper aims to scope generic transfigurations throughout the history of genres, and the way genre criticism has underlined the problem of narrativity. Since Plato and his determination of literary imitation as mimetic (dramatic), mixed (epic), and narrative (dithyramb), approaches to generic typologies were diverse. Plato’s paradigm was extended by Aristotle’s “Poetics”, and especially renewed in the period of the Renaissance. However, throughout the 20th century, genre significance is taken into a broader scope – philosophical, phenomenological, historical (or ahistorical), psychological, highlighted by evolution, factual “biological” existence (a sort of “life” of the literary work of art, as stated by Roman Ingarden), aesthetic values, inevitable generic mixtures, and stylistic choices. The simple question of the possibility of work’s existence without genre (determined a posteriori or pre-determined) propels us to observe the methodological potential of genre criticism that can result into a new theoretical approach. Our intention is to re-examine the contemporary narrative practices in one Macedonian novel (“East-West” by Jadranka Vladova and Nebojsha Knezhevic) in order to explain why narration is the most effective tool to reach for nowadays, in order to “recall-and-narrate” or to “recollect-and-tell” (according to James Olney).
Keywords: genre criticism, narrativity, memory, discourse, Macedonian postmodern novel.